The Effect of Work Discipline on Employees Performance with Motivation as a Moderating Variables in the Inspectorate Office of Musi Rawas District - Surajiyo Surajiyo; Suwarno Suwarno; Indrawati Mara Kesuma; Tri Gustiherawati (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to determine the effect of work discipline and employee performance and the influence of motivation on the relationship between work discipline and employee performance. Work discipline is an attitude that is indispensable for everyone to improve performance in order to achieve organizational goals. Motivation leads to disciplinary attitudes, high motivation for work discipline can affect employee performance. This study uses simple regression analysis and interaction test or Moderated Regression Analysis (MRA) The population in this study includes employees at the Inspectorate Office of Musi Rawas Regency. The sample of this study amounted to 68 employees, selected using a saturated sampling method. The data collection technique used a questionnaire. The results of this study indicate that work discipline has a significant effect on employee performance (Y), as evidenced by the value t_count for the Work Discipline variable (X_1) is greater than the t-table value. This indicates a significant influence between Work Discipline (X_1) on Employee Performance (Y) at the Inspectorate Office of Musi Rawas Regency. So it can be said that the hypothesis is accepted. The next result is that the motivation variable is a moderating moderating variable in the relationship between work discipline and employee performance. Motivation as a moderation variable affects the relationship between Work Discipline (X_1) and Employee Performance (Y). So, Motivation (X_2) as a Moderation variable has an effect on the relationship of Work Discipline (X_1) and Employee Performance (Y) at the Inspectorate Office of Musi Rawas Regency. Thus it can be concluded that the hypothesis is accepted. So it can be said that the Motivation variable (X_2) as a Moderation variable affects the relationship between the Work Discipline variable (X_1) on Employee Performance (Y). Motivation as a moderation variable has an influence on the relationship between work discipline and employee performance. So, giving motivation to employees is important so that giving motivation should be further improved at the Inspectorate Office of Musi Rawas Regency so that employee performance can increase even more.